2015
DOI: 10.1016/j.enconman.2015.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of piston shapes and fuel injection strategies on stoichiometric stratified flame ignition (SFI) hybrid combustion in a PFI/DI gasoline engine by numerical simulations

Abstract: a b s t r a c tIn this research, the stratified flame ignition (SFI) hybrid combustion process was proposed to enhance the control of SI-CAI hybrid combustion and moderate the maximum pressure rise rate (PRR max ) by the combination of port fuel injection (PFI) and direct injection (DI). The effect of the stratified flame formed by different piston shapes, start of direct injection (SOI) timings and direct injection ratios (r DI ) on the stoichiometric SFI hybrid combustion and heat release process was studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 47 publications
0
23
1
Order By: Relevance
“…Dam and Rutland [16] predicted the gasoline sprays from a multi-hole injector at various background temperatures (400-900 K) and densities (3-9 kg/m3) with the standard KHRT breakup model and found that it was necessary to adjust breakup model parameters, including the break-up length, as functions of the density ratio in order to accurately simulate the large-scale vapor mixing. Wang et al [17][18][19] and Bonatesta et al [20] calibrated the RD model to predict the gasoline spray and combustion process in wall-guided DI gasoline engines with the multi-hole injector. Sim et al [21] modeled the gasoline spray from an outward-opening piezoelectric injector with the modified KHRT breakup model, and the initial Sauter mean diameter (SMD) values were varied in order to validate against the measurements under different background conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Dam and Rutland [16] predicted the gasoline sprays from a multi-hole injector at various background temperatures (400-900 K) and densities (3-9 kg/m3) with the standard KHRT breakup model and found that it was necessary to adjust breakup model parameters, including the break-up length, as functions of the density ratio in order to accurately simulate the large-scale vapor mixing. Wang et al [17][18][19] and Bonatesta et al [20] calibrated the RD model to predict the gasoline spray and combustion process in wall-guided DI gasoline engines with the multi-hole injector. Sim et al [21] modeled the gasoline spray from an outward-opening piezoelectric injector with the modified KHRT breakup model, and the initial Sauter mean diameter (SMD) values were varied in order to validate against the measurements under different background conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the DI strategy, a combined PFI and DI (P-DI) strategy was applied in a gasoline engine to enable a stratified flame ignition (SFI) hybrid combustion [25,26]. In the proposed SFI hybrid combustion concept, DI was used to form a rich mixture around the spark plug in the central region of the combustion chamber and stabilize the flame kernel formation and initial flame propagation.…”
Section: Introductionmentioning
confidence: 99%
“…In the proposed SFI hybrid combustion concept, DI was used to form a rich mixture around the spark plug in the central region of the combustion chamber and stabilize the flame kernel formation and initial flame propagation. On the other hand, PFI was used to provide a lean homogenous mixture in the peripheral region and achieve a relatively moderate CAI combustion process [25,26]. The moderate heat release rate (HRR) of the SFI hybrid combustion would reduce the risk of knocking and offers a potential to improve the fuel economy by advancing the combustion phasing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these aforementioned works based on diesel engines, other similar studies were realized using biodiesel [21], gasoline [22][23][24], dual fuel [25-28] and other fuels [29][30][31][32][33][34].Numerical simulations also provide interesting information to analyze multiple injections. Particularly, in the field of Computational Fluid Dynamics (CFD), one can refer to the work of Lechner et al [35], who analyzed advanced injection strategies to achieve partially premixed combustion in a diesel engine; Sun and Reitz [36], who analyzed injection strategies to optimize two-stage combustion; Verbiezen et al [37], who analyzed the effect of injection timing; Zehni and Jafarmadar [38], who analyzed the effect of split injection in a direct-injection diesel engine; Abdullah et al [39], who analyzed the effect of injection pressure; Coskun et al [40], who analyzed second injection timings; Wang et al [41], who analyzed several fuel injection strategies on a gasoline engine; Zhaojie et al [42], who analyzed two-stage fuel injection with EGR; Lamas et al [43,44], who analyzed several configurations of pilot injections; and Sencic [45], who analyzed alternative injection patterns.Despite this literature about multiple injections, it is important to develop a reliable tool to characterize the most appropriate injection pattern. In this regard, this work presents a Multiple-Criteria Decision Making (MCDM) approach to characterize the most appropriate injection pattern.…”
mentioning
confidence: 99%
“…Numerical simulations also provide interesting information to analyze multiple injections. Particularly, in the field of Computational Fluid Dynamics (CFD), one can refer to the work of Lechner et al [35], who analyzed advanced injection strategies to achieve partially premixed combustion in a diesel engine; Sun and Reitz [36], who analyzed injection strategies to optimize two-stage combustion; Verbiezen et al [37], who analyzed the effect of injection timing; Zehni and Jafarmadar [38], who analyzed the effect of split injection in a direct-injection diesel engine; Abdullah et al [39], who analyzed the effect of injection pressure; Coskun et al [40], who analyzed second injection timings; Wang et al [41], who analyzed several fuel injection strategies on a gasoline engine; Zhaojie et al [42], who analyzed two-stage fuel injection with EGR; Lamas et al [43,44], who analyzed several configurations of pilot injections; and Sencic [45], who analyzed alternative injection patterns.…”
mentioning
confidence: 99%